1988
DOI: 10.1164/ajrccm/137.3.585
|View full text |Cite
|
Sign up to set email alerts
|

Idiopathic Pulmonary Fibrosis: Abnormalities in Bronchoalveolar Lavage Fluid Phospholipids

Abstract: Bronchoalveolar lavage has been used to sample cells and proteins in the distal lung. One of the major secretory products of the alveolar type II epithelial cells, pulmonary surfactant, can be recovered by lavage. Abnormalities in alveolar type II cells are found in biopsies of patients with idiopathic pulmonary fibrosis (IPF), and abnormalities of pulmonary surfactant phospholipids have been reported after diffuse lung injury in animals and in humans. Therefore, we questioned if abnormalities in lavage phosph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
36
2
2

Year Published

1990
1990
2007
2007

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 81 publications
(43 citation statements)
references
References 14 publications
3
36
2
2
Order By: Relevance
“…Recent studies utilizing bronchoalveolar lavage (BAL) have demonstrated that the total phospholipid concentrations as well as the ratio of phophatidylglycerol to phosphatidylinositol (PG/PI) are decreased in patients with the adult respiratory distress syndrome [3,4] and in respiratory failure due to trauma [5,6]. A reduction in the PG/PI ratio has also been observed in a variety of interstitial lung diseases [7][8][9]. Total phospholipid concentrations of bronchoalveolar lavage fluid (BALF) have been found to be diminished in patients with acquired immune deficiency syndrome (AIDS) both with and without Pneumocystis carinii pneumonia [10,11].…”
mentioning
confidence: 99%
“…Recent studies utilizing bronchoalveolar lavage (BAL) have demonstrated that the total phospholipid concentrations as well as the ratio of phophatidylglycerol to phosphatidylinositol (PG/PI) are decreased in patients with the adult respiratory distress syndrome [3,4] and in respiratory failure due to trauma [5,6]. A reduction in the PG/PI ratio has also been observed in a variety of interstitial lung diseases [7][8][9]. Total phospholipid concentrations of bronchoalveolar lavage fluid (BALF) have been found to be diminished in patients with acquired immune deficiency syndrome (AIDS) both with and without Pneumocystis carinii pneumonia [10,11].…”
mentioning
confidence: 99%
“…Very few studies have examined Lype II cell function under conditions of naturally occurring or chemically induced lung disease. Perturbations of the surfactant system accompany a number of human respiratory conditions, including the neonatal and adult respiratory distress syndromes (4,5), idiopathic pulmonary fibrosis (6), and alveolar proteinosis (7,8), but the causes of the surfactant abnormalities and their relationship to the progression of disease have not been delineated. In addition, in experimental animals, alterations in surfactant levels have been reported following exposure of the lung to a variety of chemical and physical agents, suggesting that Type II cells and the surfactant system may be important components in the response ofthe lung to irnury.…”
mentioning
confidence: 99%
“…A limited degree of lipidosis may then determine the induction ofdiffuse interstitial fibrosis instead of the focal or circumscribed forms of dust lesions characteristic of simple silicosis, coal workers' pneumoconiosis and asbestosis (316). Human pulmonary interstitial fibrosis affords a comparable situation, since the more severe fibrotic features were associated with a reduction ofphospholipid in bronchoalveolar lavage fluid (317). The proposal that surface radicals exposed on freshly fractured particles of crystalline silica are implicated in the genesis ofaccelerated silicosis (318) or that such radicals account for pulmonary injury by fresh coal mine dust (205) …”
Section: Lipid Interventionmentioning
confidence: 99%